The Effect of Monopoly Power, Asymmetric Information, Transparency and Accountability Towards Intent to Adopt E-Procurement - H Habiburrochman; Siti Fatimah (Indonesian Journal of Law and Economics Review, 2020)
One of the benefits of e-procurement implementation in reducing corruption in public procurement process, to create good governance. Factors that affect corruption in public procurement process are monopoly power, asymmetric information, and lack of transparency and accountability. This study aims to determine. This research is expected to provide an overview of the potential and benefit of e-procurement in reducing corruption, increasing awareness towards the risk of fraud in public procurement, and provide a contribution to create good governance. The object in this study is the state university in Surabaya. A questionnaire is used to collecting the data, with total respondents are 70 officials. The result from this study shows that independent variable such as monopoly power, information asymmetric, transparency, and accountability have a significant effect on the intention to adopt e-procurement. Support from officials has a significant impact on the adoption of e-procurement.